PENGGUNAAN MODEL WORD SQUARE UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS V SD NEGERI 001 SEDINGINAN KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Syahrial '; Suarman '; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the Model Word Square Application Usage To Increase Motivation At Subjects IPS Student Class V SD Negeri 001 Sedinginan Tanah Putih Rokan Hilir with a total of 25 students. This research was conducted in several cycles with the subject of class V students of SD Negeri 001 Sedinginan Tanah Putih Rokan Hilir 2015/2016. Based on the survey results revealed that the Model Word Square can increase learning motivation IPS fifth grade students of SD Negeri 001 Sedinginan Tanah Putih Rokan Hilir. Activities teachers first cycle result is 43.7% in the category are not perfect and the second cycle has reached a success rate of 78.1% in the category that is perfect. Student activity cycle I result already achieved a success rate that is 50.5% and in the second cycle, the better the score with a score that is 84% in the very high category. Student motivation first cycle results are already achieved a success rate that is 52% and the second cycle has reached a success rate of 84% in the category of very high interval.Keyword: Motivation Learning Student. Word Square model